Mae. Volume two - Ha, Gene; Waid, Mark, 1962-; Kremer, Molly Jane (Roar, 2019)
"Mae has followed her long-lost sister Abbie through a gate and into another world: Cimrterén, a world full of dangerous creatures, strange science, and warring nobles. Their father has gone missing, and Mae and Abbie must fight their way to the heart of Ebenhrad to find their father. Along their journey, they'll come across old friends as well as some new adversaries determined to stand in their way. ... Mae and Abbie face some of their biggest challenges yet. When the sisters get separated, Mae learns that navigating her own way through the Other World isn't as easy as she thought. Luckily, her old friend Dahlia is prepared to join Mae on her journey through Cimrterén. Together, on their search for Abbie and the sisters' father, they begin to uncover sinister secrets at the heart of Zemětřasi and Obrůoni forces. Soon, they'll meet a new foe that even the greatest powers of Cimrterén fear. And they will face him alone."--